Omorgus (Omorgus) khandesh (Coleoptera: Scarabaeoidea: Trogidae), a new species from India, along with an annotated catalogue of the Oriental and Palearctic species of the subgenus Omorgus Erichson, 1847 - Strümpher, Werner P.; Kalawate, Aparna S. (Zootaxa, 2023)
A new species of keratin beetle from Western India, Omorgus (Omorgus) khandesh Strümpher & Kalawate, new species, is described and illustrated. The new species is morphologically most similar to O. (O.) rimulosus (Haaf, 1957). The latter is redescribed and illustrated to enable accurate recognition of both species. Based on this work the following taxonomic changes are proposed: Three species are transferred from the subgenus Afromorgus Scholtz, 1986 to the nominotypical subgenus: O. (O.) inclusus (Walker 1858), O. (O.) maissouri (Haaf, 1945a) and O. (O.) rimulosus (Haaf, 1957). Lastly, we include an annotated catalogue of the species of the nominotypical subgenus Omorgus known from the Oriental and Palaearctic regions.